PENGARUH MODEL PEMBELAJARAN QUANTUM LEARNING TERHADAP KEMAMPUAN MEMAHAMI ISI BACAAN PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS V SDN 1 PAREMAS KECAMATAN JEROWARU - BAIQ SOLATIAH; M. DENI SIREGAR; ZUFADLI HAMDI; MUHAMMAD SURURUDDIN (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this study was to determine the effect of the Quantum Learning Model on the Ability to Understand Reading Content in Indonesia Language Learning for Grade V Student of SDN 1 PAREMAS, Jerowaru District. The research used was a quantitative method with an experimental research theme. The research used a pre-experiental design with a one-grouppretest-posttest type. The population that became the subject of this study were all students at SDN 1 PAREMAS. Based on the data obtained, it was known that the pretest csore on the result obtained was 129 and the posttest score was 162. The result of the pretest normality test for the ability to understand the content of students’ readings were obtained by a count of 0.840 with an it table value of 0.0220, so that the count <it table. While the value of the posttest normality test result obtained by a count of 0.899. with an it table value of 0.220, so that tce count<it table. This shows that the data from the pretest and posttest result for the ability to understand the content of students’ readings were normality distribused.